2012
DOI: 10.1590/s0100-69912012000300007
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo de aderências intraperitoneais associadas ao uso das telas de polipropileno e de malha leve de polipropileno revestida com ácido graxo ômega-3

Abstract: OBJETIVO: Comparar as aderências entre dois grupos de ratas Wistar submetidas à colocação intraperitoneal da tela de polipropileno e malha leve de polipropileno revestida com ácido graxo ômega-3. MÉTODOS: Foram utilizadas 27 ratas Wistar randomizadas em três grupos. No grupo 0 não houve colocação de prótese, no grupo 1 houve implantação da prótese de polipropileno e no grupo 2, implantação de prótese de polipropileno revestida com ácido graxo ômega-3. Foi avaliadas a presença de aderências, grau, força de rupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…When inserted intraperitoneally, in general a mesh induces a foreign body reaction and the Experimental studies with surgical meshes for evaluation of biocompatibility and adhesion formation use animal models, such as rabbits [23][24][25] , sheep 26 , pigs 15 , and, especially, rats 11,27 . The variables analyzed include incidence, extent, quality and, in some studies, resistance to rupture and tenacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When inserted intraperitoneally, in general a mesh induces a foreign body reaction and the Experimental studies with surgical meshes for evaluation of biocompatibility and adhesion formation use animal models, such as rabbits [23][24][25] , sheep 26 , pigs 15 , and, especially, rats 11,27 . The variables analyzed include incidence, extent, quality and, in some studies, resistance to rupture and tenacity.…”
Section: Discussionmentioning
confidence: 99%
“…Consecrated by its excellent biocompatibility, incorporation, maintenance of abdominal wall traction and low cost, it is associated with a high incidence of adhesions 14,22 . In experimental studies, the formation of adhesions is observed in 100% of meshes, covering from 50% to 100% of their surface 11,12,27 . The authors described the omentum as the most often involved structure, followed by the liver and the bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors such as smoking, factors that are inherent to the patient as obesity and genetics, as well as local complications of the incision, with wound infection, are important to the development of incisional hernias 13 15 26 . Published articles on the various options of synthetic prostheses used in the repair of such hernias 1 3 9 18 19 22 23 29 show that even the state-of-the-art materials, developed for direct contact with the abdominal cavity, despite decreasing, they can not completely prevent the formation of adhesions on these prostheses 4 22 23 25 , demonstrating that these materials need to be improved. Several experimental studies describe tactics to minimize complications related to adhesions 2 14 20 27 and implanted biomaterials 3 6 16 .…”
Section: Discussionmentioning
confidence: 99%
“…They can be basically divided on: 1) those which an incision is made with standard size on the linea alba and its repair is made with different prostheses in the first operation 11 19 21 ; 2) on those that resect fragments with various formats of the wall 9 22 23 30 and also perform primary repair 1 10 29 ; and on 3) those whose model is similar to the usual clinical condition, initially producing an incisional hernia, with its subsequent correction 4 . The focus of these studies is the consequence of the synthetic implants directly in contact with the abdominal viscera, a topic that has gained importance with the development of laparoscopy as an option for treating ventral hernias 5 16 18 25 . From the experimental point of view, many authors make no distinction between such options, also calling incisional hernia when defects of abdominal wall are fixed in the first surgery 6 25 29 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation